XMM-Newton High-resolution Spectroscopy of EXO 0748–676 after Its Reemergence from a Long Quiescence - Sayantan Bhattacharya; Sudip Bhattacharyya; Gargi Shaw (The Astrophysical Journal Letters)
EXO 0748–676 is a well-studied, high-inclination, dipping and eclipsing neutron star low-mass X-ray binary that has recently emerged from 16 yr of quiescence into a new outburst. We present results from 55.5 ks of XMM-Newton observation, focusing on high-resolution spectroscopy with the same instrument (the Reflection Grating Spectrometer) that produced significant insights during the previous outburst. The XMM-Newton European Photon Imaging Camera light curve reveals a type I X-ray burst that leads to a corresponding optical burst by 3 s. To understand the effects of the burst on the ionization structure, the data are divided into burstless and pre- and postburst spectra, with additional analysis for dip and nondip phases. The primary spectral feature in all phases is a broad O vii recombination line, accompanied by velocity-broadened O viii , N vii , and Ne ix lines. Notably, the Ne ix line shows different ionization states for the preburst (11.65 Å) and postburst (13.56 Å) phases, while the dips also substantially affect the spectral lines. The current outburst mirrors many traits from the earlier one, such as a similar spectral state, plasma components with similar ionization structure, and spectral features from the same elements, implying a stable long-term accretion behavior across outbursts.